Discharge Planning to Improve Readiness Transition Care in-Patient Cerebrovaskuler Accident: A Literature Review - Apriyani Puji Hastuti; Nursalam; Fitri Chandra Kuspita; Lina Ema Purwanti; Domingos Soares; Misutarno; Karyo; Ismuntania; Ratna Roesardhyati (Journal Of Nursing Practice, 2023)
Background: Effective and continuity discharge planning is vital in care continuity and integrated care. Continuity discharge planning can reduce avoidable hospital readmission, and fulfillment improves the quality of care. Prevention efforts to prevent the re-attacks and readmission because of this CVA attack should be started early before the patients return home from the hospital. Purpose: This research aims to review the effect of discharge planning on the readiness of returning home in CVA patients. Methods: We included english materials published between Science Direct, PubMed, Research Gate, and Google Scholar that were used to find studies on discharge planning, readiness, and transitional care between 2016- 2021. Results: Discharge planning is carried out in three-stage, inpatient admission and intra-hospital when the patient is about to be discharged from the hospital. In the first stage, the nurse explains patient admission, regulation, and management when the patient enters the hospital. The second stage is when the patient is hospitalized, which consists of nurses providing education about medication, environment, health, outpatient referral, and diet. While the last stage is when the patient will be discharged, the nurse explains the control, medication, and nutrition schedule at home. Post-stroke rehabilitation and recovery is a chronic process. Conclusion: Review of discharge planning can be influenced by several factors: individual characteristics (clients' potential with special needs early, motivation), family factors (social resources, home environment), and health care system (teaching home care skills with community/ hospital professionals. These factors will affect the implementation of discharge planning in health services which is hospital accreditation.